Pengembangan Kuis Interaktif Berbasis E-Learning dengan Menggunakan Aplikasi Wondershare Quiz Creator pada Mata Kuliah Belajar dan Pembelajaran Matematika - Meryansumayeka; Virgiawan, M. Dimas; Marlini, Sri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
This study aims to develop an interactive quiz on e-learning in Teaching and Learning Mathematics Course by using Wondershare Quiz Creator application. Type of research is a developmental research modified between Rowntree and Tessmer. There are 3 stages in this research namely planning stage, development stage, and evaluation stage. In the process of development, this research involves the experts as validators of interactive quiz developed. The subjects of this study were all students who take Teaching and Learning Mathematics Course in 2016/2017 academic year. The results of this study show that the interactive quiz developed by these researchers was valid based on experts comment on material aspects, media display and instructional design; practice based on research results on a one-on-one scale of testing products on 3 different students and on a small group scale that requires 6 people; and effective in terms of time and economy based on trial results.